2010
DOI: 10.1038/hr.2010.121
|View full text |Cite
|
Sign up to set email alerts
|

Is overall blockade superior to selective blockade of adrenergic receptor subtypes in suppressing left ventricular remodeling in spontaneously hypertensive rats?

Abstract: To test the hypothesis that nonselective blockade of adrenergic receptor (AR) subtypes is superior to selective blockade of AR subtypes in suppressing left ventricular (LV) remodeling induced by hypertension. Sixty-four spontaneously hypertensive rats (SHR) were randomly divided into four groups: bisoprolol-treated, propranolol-treated, carvedilol-treated and no treatment groups (n¼16, each). Sixteen Wistar-Kyoto (WKY) rats served as a control group. Echocardiography and cardiac catheterization were carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Previous studies demonstrated that apoptosis is involved in the cardiac remodelling and substantial loss of cardiomyocytes in genetic hypertension [36] and in renovascular hypertension [37]. Cardiomyocyte apoptosis enhances the cardiac remodelling of hypertensive rats and affects the cardiac interstitium [38]. Cardiomyocyte apoptosis induced by prenatal exposure to LPS may cause myocardial remodelling in the current study.…”
Section: Discussionsupporting
confidence: 47%
“…Previous studies demonstrated that apoptosis is involved in the cardiac remodelling and substantial loss of cardiomyocytes in genetic hypertension [36] and in renovascular hypertension [37]. Cardiomyocyte apoptosis enhances the cardiac remodelling of hypertensive rats and affects the cardiac interstitium [38]. Cardiomyocyte apoptosis induced by prenatal exposure to LPS may cause myocardial remodelling in the current study.…”
Section: Discussionsupporting
confidence: 47%
“…The results of this study have important clinical significance in the treatment of hypertension complicated with respiratory diseases. It is known that the α1 receptor is mainly distributed in vascular smooth muscle, the β1 receptor is mainly distributed in cardiac muscle, and the β2 receptor is distributed in both vascular and bronchial smooth muscle ( O-Uchi and Lopes, 2010 ; Chen et al, 2010 ). As a result, patients with a combination of respiratory disease and hypertension have poor tolerance to non-selective beta blockers.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Chen et al found decreases in the expression levels of b-ARs (b 1 -and b 2 -AR) due to enhanced sympathetic stimulation, which recovered spontaneously in hypertensive rats treated with AR antagonists. 10 Moreover, the expression level of b 2 -AR was increased in proportion to b 1 -AR in the carvedilol-treated group compared with animals treated with propranolol (a b 1 -and b 2 -AR antagonist); however, carvedilol is known to be relatively selective to b 1 -AR. 12 This specific recovery of b 2 -AR signaling by carvedilol may, in part, contribute to the attenuation of cardiomyocyte apoptosis.…”
mentioning
confidence: 99%
“…9 Here, three important questions have been raised: (1) In this issue of Hypertension Research, Chen and colleagues test the hypothesis that non-selective AR blockade is more efficient in suppressing LV remodeling when compared with AR subtype-selective antagonists in a spontaneously hypertensive rat model. 10 A previous study compared non-AR subtype-selective and AR subtype-selective inhibition on LV dysfunction and remodeling induced by chronic coronary stenosis and coronary occlusion, 11 showing benefit from a non-selective inhibitor; however, a detailed mechanism was not investigated in that study. Chen and colleagues compared the effect of the b 1 -AR antagonist bisoprolol, the b 1 -and b 2 -AR antagonist propranolol and the a 1 -, b 1 -and b 2 -AR antagonist carvedilol on LV remodeling by hypertension (see also Figure 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation